The impact of the European patent system on SMEs and national states. (1st March 2020) - Xenos, Dimitris
Abstract : A centralized and federal patent system in the EU changes economic and constitutional law structures by creating a 'nationalized' international patent. As the underlying economic policy has concentrated on the development needs of small and medium-sized enterprises (SMEs), accounting for 99% of all businesses in Europe, statistical analysis and data of their patenting activity and patent ownership are used to assess whether the new regime can help or hinder SMEs and the states in which they are based. Due consideration is given to the monopoly effect of patents and the adversarial nature of the judicial, federal system that is introduced in the absence of a federation of states. Although there are always costs and benefits in such a system, new legal/institutional developments amplify existing imbalances in technological and economic capacities between and within member states, and between them and non-EU states.